2012
DOI: 10.1016/j.infrared.2012.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Medical applications of infrared thermography: A review

Abstract: The primary objective of this study is the development of transparent thin film materials in the IR enabling strong infrared absorption of organic compounds in the vicinity of metal nanoparticles by the surface plasmon effect. For developing these optical micro-sensors, heterostructures combining gold nanoparticles and chalcogenide planar waveguides are fabricated and adequately characterized. Single As 2 S 3 and Ge 25 Sb 10 Se 65 amorphous chalcogenide thin films are prepared by radiofrequency magnetron sputt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
610
0
22

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 986 publications
(689 citation statements)
references
References 141 publications
3
610
0
22
Order By: Relevance
“…Additionally, many protocols of studies, in which sample are people with certain diseases (as, for example, diabetes), they use to set the acclimatizing time on 15 min [28].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, many protocols of studies, in which sample are people with certain diseases (as, for example, diabetes), they use to set the acclimatizing time on 15 min [28].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that PpIX metabolism is faster at higher temperatures 31,32 . Skin temperature varies at different body sites and can be displayed with infrared imaging cameras 33 [http://www.rnhrd.nhs.uk/page/92]. Typical temperatures of the head and the neck have found to be 35-37°C 34,35 , the lower leg and the "edge" areas of the feet and the hands have lower temperatures of 30-33°C.…”
Section: Ppix Fluorescence Correlation To the Body Sites: Does Skin Tmentioning
confidence: 99%
“…4,18 Some studies have shown the significance of thermography in the estimation of some painful conditions, including radiculopathy. 4,8,10,[18][19][20] Contrary to the methods that estimate radiculopathy on the basis of structural changes in the spine or changes in spinal nerve root function, IRT assesses radiculopathy based on a vasomotor dysfunction. Its advantage in comparison with other methods is its non-invasive, painless nature that does not expose the patient to ionising radiation and is also easy to use.…”
Section: Discussionmentioning
confidence: 99%